The case for a European Defence Review: Why national-level armed forces planning is not enough - Marcel Dickow; Hilmar Linnenkamp; Christian Mölling (Stiftung Wissenschaft und Politik (SWP), 2012)
The EU's Common Security and Defence Policy (CSDP) is on the verge of collapse due to a lack of common resources and capabilities. Indeed, the EU Member States have an excess of some things, such as frigates and fighter aircraft, but an inadequate supply of other important components, including aerial refueling and reconnaissance capabili-ties. This is primarily because national preferences and traditions continue to play the decisive role in European defence planning. Despite the financial crisis and resulting austerity measures - and despite the often reiterated commitment to the CSDP vision - there is still a lack of resolve among EU Member States to building common ground in security and defence policy. It is not enough to seek cooperation in isolated areas through the pooling and sharing of capabilities or to announce the advent of "smarter defence". These measures will not be enough to move armed forces development from the narrow national level to a broader European base. A European Defence Review would establish a new point of departure for the development and coordination of the required capabilities. National military planning - an ongoing element of national sovereignty - requires such a framework if it is to be useful for the CSDP
Keywords: 320